(untitled) (Revista Inclusiones, 2020)
The purpose of the article is to study the dominant coping-strategy of the personality and indicators of well-being, activity and mood of junior and senior cadets-sailors; holding a comparative analysis of psychophysiological changes after a long voyage. The following methods were used: observation, conversation, methodology “Indicator of coping-strategies”, methodology “Well-beingactivity-mood”. It is defined that the leading coping-strategy for junior cadets is the search for social support and for senior cadets – avoiding problems. Comparative characteristics of the indicators of well-being, activity and mood demonstrates a decrease after cadets’ long-term floating practice indicators of well-being, health complaints; an increase of activity indicators, as the need to be more energetic in finding solutions to life’s problems. A decrease of mood indicators was recorded in respondents as an indicator of dissatisfaction with oneself. It has been substantiated that the value of the study is the identification of the connection between the elements of maladjustment and the fact of being in a long voyage. The need for further research of psychophysiological parameters, behavioral models of future sailors is indicated. The prospects for the study of psychophysiological parameters of a cadet-sailor are indicated, taking into account the type of his professional duties.